Exploring the knowledge of Islamic banking among Libyan bankers - El-Brassi, Mohamed A. M. Abdelrahim; Syed Jaafar Alhabshi, Syed Musa; Othman, Anwar Hasan Abdullah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Although it has been five years since the beginning of the conversion to the Islamic banking system (IBS) in Libya., the level of knowledge of Islamic banking (IB) products and services among bankers is yet to be investigated. The study uses a quantitative research design to address the issue. A total of 207 complete and valid questionnaires were collected from bankers in several Libyan commercial banks. Statistical Package for Social Sciences SPSS version 23.0 was employed to analyze the data. Findings showed that bankers have a basic to moderate level of knowledge of IB services and products. They were unaware of some important Islamic services and products such as Musharakah, Murabahah to the purchase ordered (MPO), current Islamic account and investment banking account. The findings also concluded that the bankers were only knowledgeable about concepts of Islamic principles such as the permissibility of selling and prohibition of riba. However, they were unaware of how riba is applied in the banking system. This study urges relevant Libyan stakeholders such as government and top bank management to develop intensive Islamic banking training programs. In order to increase the level of knowledge and awareness of bankers towards IB. This would help to facilitate the conversion to (IBS) in the country.